The Accumulation of Surplus Property According to Islamic Law - Mücahit Turgut (İslam Tetkikleri Dergisi)
This paper discusses the basic principles of Islamic economy and investigates whether the permissibility of accumulating surplus goods. In the introduction, the importance of the subject is examined, in both past and contemporary contexts. In the main part, doctrines on the accumulation of property are described. Various perspectives on the conditions and circumstances necessary for the accumulation of property are examined. Opinions on the subject from past to present are discussed from an objective point of view and are evaluated in the light of the basic sources. It is determined that, under normal conditions, there is a right to private property in Islam, and the property that individuals accumulate cannot be touched by the state except under conditions of necessity and for the public benefit. Alternatives related to assistance and solidarity havebeen developed in Islam to meet basic needs in society, but this study concludes that those with surplus goods have a religious responsibility; their financial responsibilities do not consist only of zakat.